Chronic Inhibition of mROS Protects Against Coronary Endothelial Dysfunction in Mice With Diabetes - Xing, Hang; Zhang, Zhiqi; Shi, Guangbin; He, Yixin; Song, Yi; Liu, Yuhong; Harrington, Elizabeth O.; Sellke, Frank W.; Feng, Jun (Frontiers in Cell and Developmental Biology, 2021)
Diabetes is associated with coronary endothelial dysfunction. Persistent oxidative stress during diabetes contributes to coronary endothelial dysfunction. The mitochondria are main sources of reactive oxygen species (ROS) in diabetes, and mitochondria-targeted antioxidant mito-Tempo can prevent mitochondrial ROS (mROS) generation in a variety of disorders. Inhibition/inactivation of small-conductance Ca2+-activated K+ (SK) channels contribute to diabetic downregulation of coronary endothelial function/relaxation. However, few investigated the role of mROS on endothelial dysfunction/vasodilation and endothelial SK channel downregulation in diabetes. The aim of present study was to investigate the chronic administration of mito-Tempo, on coronary vasodilation, and endothelial SK channel activity of mice with or without diabetes. Mito-Tempo (1mg/kg/day) was applied to the mice with or without diabetes (n = 10/group) for 4 weeks. In-vitro relaxation response of pre-contracted arteries was examined in the presence or absence of the vasodilatory agents. SK channel currents of the isolated mouse heart endothelial cells were measured using whole-cell patch clamp methods. At baseline, coronary endothelium-dependent relaxation responses to ADP and the selective SK channel activator NS309 and endothelial SK channel currents were decreased in diabetic mice compared with that in non-diabetic mice (p<0.05). After 4-week treatment with mito-Tempo, coronary endothelium-dependent relaxation response to ADP, NS309 and endothelial SK channel currents in the diabetic mice was significantly improved when compared with that in untreated diabetic mice (p<0.05). Interestingly, coronary relaxation responses to ADP and NS309 and endothelial SK channel currents were not significantly changed in non-diabetic mice after mito-Tempo treatment compared to that of untreated control group. Chronic inhibition of endothelial mROS appears to improve coronary endothelial function/dilation and SK channel activity in diabetes, and mROS inhibitors may be a novel strategy to treat vascular complications in diabetes.